Synthesis of calcium propionate from indigenous limestone from Swat area in Pakistan - Mahmood, Ansar; Zahra, Samreen; Mahmood, Rashid; Sheikh, Asma (European Journal of Chemistry, 2023)
In this study, native limestone from the Swat area of Pakistan was used for the synthesis of calcium propionate. The powdered limestone was allowed to react with propionic acid and the effect of the synthesis parameters, that is, the particle size (50, 100, 150, and 200 mesh), propionic acid (10, 15, and 30 %), solid-liquid ratio (0.1:10, 0.12:1, 0.14:1, and 0.16:1), reaction time (1, 1.5, 2, and 2.5 hours) and the temperature (60, 80, 90, and 100 °C) on the percentage yield and purity of calcium propionate was studied. The results showed that the optimum synthesis parameters were 200 mesh particle size, 15% propionic acid concentration, 0.14:1 solid-liquid ratio, 2.5 hours reaction time, and 80 °C temperature. The product obtained under optimal conditions was characterized by infrared spectroscopy, thermogravimetry, and scanning electron microscopy. The results revealed that a product having ≥ 99.8% purity with 85% yield can be obtained by this process.